Strategies of expressing written apologies in the online newspaper - Cipto Wardoyo (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2014)
Expressing apology is a universal activity although people have different strategies or ways to express the apology based on the culture, situation, and context. An apology has played a vital role in verbal politeness; it is certainly impolite when someone does not express an apology when he or she has commited an offence to the others. Apologies in the Pragmatic study is classified under speech act theory. An apology based on Searle (1969) is classified as expressive speech acts because it expresses speaker’s physiological attitude. An apology expresses speaker’s sorrow and regret because he/she has offended hearers or readers. This paper tries to discuss strategies of editors in expressing written apologies in the online newspaper. The objective of this paper is to explain what the strategies of written apologies are in the online newspaper. This study uses qualitative method; the writer chooses descriptive interpretative technique for analyzing data. There are four written apologies in the online neswpapers as data sources in this paper, the data are taken from The Jakarta Post, The Daily Express, The Sun, and Brisbane Times. The writer tries to describe and analyzes utterances in the data sources based on Olshtain & Cohen theory (1986). There are five main strategies in expressing apologies according to Olshtain & Cohen (1986); they are Illocutionary Force Indicating Device (IFID), expression responsibility, explanation/justification, offer repairs, and promise forbearance. The writer found that all of the written apologies used combination strategies, they used IFID by using performative verb: apologize and be sorry then followed by expression resposbility, explanation, offer repairs, and promise forbearance.